Fantastic beasts and where to find them - Scamander, Newt; Rowling, J. K. (Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
Offers alphabetically arranged entries detailing the characteristics of such mythical beasts as hippogriffs, blast-ended skrewts, dragons, and unicorns.